Should anaesthesia method for prostate biopsy be the same for every patient? A randomised prospective study to determine the risk factors for pain - Avcı, Sinan; Oner, Sedat; Önen, Efe; Çağlayan, Volkan; Kılıç, Metin; Şambel, Murat (The European Research Journal, 2020)
Objectives: To evaluate the risk factors for pain occurring during prostate biopsy.Methods: This study included 123 patients were applied with prostate needle biopsy under transrectal ultrasonography. The patients were randomly separated into 3 groups of 41 individuals. For periprostatic nerve blockage, 10 cc 2% lidocaine was applied to Group 1, 10 cc 0.25% levobupivacaine to Group 2, and 10 cc 0.25% bupivacaine to Group 3. A 10 cm Visual Analogue Scale (VAS) was used to evaluate patient pain. The pain of the patients was evaluated in 4 stages. VAS 1: Pain score during the injection of the anaesthetic agent; VAS 2: Pain score during the biopsy when half the procedure was completed; VAS 3: Pain score following removal of the rectal probe immediately after the biopsy; and VAS 4: Pain score at 1 hour after the biopsy.Results: There were significant negative correlations between VAS 3 pain scores and age in group 1, group 3 and for entire cohort (p = 0.013, p = 0.031 and p = 0.033, respectively). In group 1 both total and free PSA showed significant negative correlations with VAS 3 pain scores (p = 0.020 and p = 0.010, respectively). In group 2 VAS 4 pain scores of the patients with suspicious digital examination findings were found to be significantly higher than those of the patients with benign digital examination findings (p = 0.025).Conclusions: Of all patients to be applied with prostate biopsy, those of a younger age, with a lower PSA level, with suspicious digital rectal examination findings constitute a relatively higher risk group in respect of pain.